Transcriptional Effects of Ozone and Impact on Airway Inflammation - Mumby, Sharon; Chung, Kian Fan; Adcock, Ian M. (Frontiers in Immunology, 2019)
Epidemiological and challenge studies in healthy subjects and in individuals with asthma highlight the health impact of environmental ozone even at levels considered safe. Acute ozone exposure in man results in sputum neutrophilia in 30% of subjects particularly young children, females and those with ongoing cardiopulmonary disease. This may be associated with systemic inflammation although not in all cases. Chronic ozone exposure amplifies these effects and can result in the formation of asthma-like symptoms and immunopathology. Asthmatics who give a functional response to ozone (responders) induce a greater number of genes in bronchoalveolar (BAL) macrophages than healthy responders with up-regulation of inflammatory and immune pathways under the control of cytokines and chemokines and the enhanced expression of remodelling and repair programmes including those associated with protease imbalances and cell-cell adhesion. These pathways are under the control of several key transcription regulatory factors including nuclear factor (NF)-B, anti-oxidant factors such as nuclear factor (erythroid-derived 2)-like 2 Nrf2, the p38 mitogen activated protein kinase (MAPK) and priming of the immune system by up-regulating toll-like receptor (TLR) expression. Murine and cellular models of acute and chronic ozone exposure recapitulate the inflammatory effects seen in humans and enable the elucidation of key transcriptional pathways. These studies emphasise the importance of distinct transcriptional networks in driving the detrimental effects of ozone. Studies indicate the critical role of mediators including IL-1, IL-17 and IL-33 in driving ozone effects on airway inflammation, remodelling and hyperresponsiveness. Transcription analysis and proof of mechanisms studies will enable the development of drugs to ameliorate the effects of ozone exposure in susceptible individuals.